Medicare's hospital readmissions reduction program and the rise in observation stays. (27th February 2023) - Wright, Brad; Parrish, Canada; Basu, Anirban; Joynt Maddox, Karen E.; Liao, Joshua M.; Sabbatini, Amber K.
Abstract: Objective: To evaluate whether Medicare's Hospital Readmissions Reduction Program (HRRP) is associated with increased observation stay use. Data Sources and Study Setting: A nationally representative sample of fee‐for‐service Medicare claims, January 2009–September 2016. Study Design: Using a difference‐in‐difference (DID) design, we modeled changes in observation stays as a proportion of total hospitalizations, separately comparing the initial (acute myocardial infarction, pneumonia, heart failure) and subsequent (chronic obstructive pulmonary disease) target conditions with a control group of nontarget conditions. Each model used 3 time periods: baseline (15 months before program announcement), an intervening period between announcement and implementation, and a 2‐year post‐implementation period, with specific dates defined by HRRP policies. Data Collection/Extraction Methods: We derived a 20% random sample of all hospitalizations for beneficiaries continuously enrolled for 12 months before hospitalization ( N = 7, 162, 189). Principal Findings: Observation stays increased similarly for the initial HRRP target and nontarget conditions in the intervening period (0.01% points per month [95% CI −0.01, 0.3]). Post‐implementation, observation stays increased significantly more for target versus nontarget conditions, but the difference is quite small (0.02% points per month [95% CI 0.002, 0.04]). Results for the COPD analysis were statistically insignificant in both policy periods. Conclusions: The increase in observation stays is likely due to other factors, including audit activity and clinical advances.